Shaping Consumer Perceptions of Genetically Modified Foods: The Influence of Engineering, Science, and Design Signifiers in Packaging Disclosure Statements - Bryan F. Howell; Ellyn M. Newcomb; D. Wendell Loh; Asa R. Jackson; Michael L. Dunn; Laura K. Jefferies (Foods)
Genetically modified (GM) foods have existed for decades, and governments internationally have legislated packaging disclosure statement language that typically incorporates the words genetic, modified, and organism. In 2018, the United States implemented the National Bioengineered Food Disclosure Standard (NBFDS) and introduced the term Bioengineered (BE) into GM disclosure language to help clarify consumer uncertainty regarding GM foods. Since then, the US consumer attitudes, perceptions, and knowledge of genetically modified foods remain negative, reflecting a contaminated interaction. Current mandated disclosure labels, utilizing engineering and science-based signifiers, are associated with this negative interaction. This research assesses whether food disclosure labels based on the signifier Design, unassociated with current contaminations, can positively impact the consumer perception of GM foods compared to the negatively contaminated science and engineering signifiers currently used. Two online studies of 1931 participants analyzed GM/BE food disclosure labels comparing four existing and six newly created engineering and science-based signifiers against four new design-based signifiers across fifteen attributes, including Price, Purchase Likelihood, Environmental Impact, Fair Trade, Safety, Nutrition, Healthfulness, Quality, Eating Experience, Comforting, Inviting, Frightening, Understandable, Ethical, and Sustainable. Across both studies, design-related labels consistently outperformed traditional engineering/science-based terms in fostering positive perceptions. However, even the best-performing labels did not fully overcome the entrenched skepticism associated with GM foods, underscoring the need for complementary strategies beyond linguistic changes.